(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, a scientific analysis was carried out of the fact that along with the concept of social justice, there is a concept of social equality, that social justice as an ambiguous and multifaceted scientific category associated with morality, spirituality, philosophy of law and branches of law, presents society with very diverse ideas of justice. Modern science considers the study of justice as a phenomenon contradictory, which is explained by the problem-design nature of modeling in society at the present stage of its development. Social justice is understood as ensuring the employment of every able-bodied person, receiving a decent salary, social security for disabled people and children without parents, providing citizens with education, healthcare, culture, sports, etc. In a market economy, competition forces an entrepreneur to direct his efforts to meet the needs of society. But with a proper understanding of the market requirements, this will not prevent a successful entrepreneur from getting rich. This creates a powerful impetus for entrepreneurial activity, serves the development of the economy. But at the same time, the market system generates social injustice in society.